Leishmaniavirus genetic diversity is not related to leishmaniasis treatment failure. (February 2021) - Ginouvès, M.; Couppié, P.; Simon, S.; Bourreau, E.; Rogier, S.; Brousse, P.; Travers, P.; Pommier de Santi, V.; Demar, M.; Briolant, S.; Prévot, G.
Abstract: Objectives: The outcome of American tegumentary leishmaniasis (ATL) may depend on the presence of the Leishmania RNA virus (LRV). This virus may be involved in treatment failure. We aimed to determine whether genetic clusters of LRV1 are involved in this therapeutic outcome. Methods: The presence of LRV1 was assessed in 129 Leishmania guyanensis isolates from patients treated with pentamidine in French Guiana. Among the 115 (89%) isolates found to carry LRV1, 96 were successfully genotyped. Patient clinical data were linked to the LRV data. Results: The rate of treatment failure for LRV1-positive isolates was 37% (15/41) versus 40% (2/5) among LRV1-negative isolates (p 0.88). Concerning LRV1 genotypes, two predominant LRV1 groups emerged, groups A (23% (22/96)) and B (70% (67/96)). The treatment failure rate was 37% (3/8) for group A and 45% (9/20) for group B (p 0.31). Discussion: Neither the presence nor genotype of LRV1 in patients with L. guyanensis seemed to correlate with pentamidine treatment failure.